Beneficial Microorganisms in Agriculture, Aquaculture and Other Areas - Liong, Min-Tze.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book focuses on the use of microorganisms in relation to agriculture, aquaculture and related fields, ranging from biofertilizers to poultry production. The latest innovations are also included to provide insights into the unlimited potentials of microorganisms in these areas. Individual chapters explore topics such as probiotics in poultry, biopurification of wastewater, converting agrowastes into value-added applications and products, rice cultivation, surfactants and bacteriocin as biopreservatives, bioplastics, crop productivity, biofloc, and the production of natural antibiotics. This volume will be of particular interest to scientists, policymakers and industrial practitioners working in the fields of agriculture, aquaculture and public health.
Probiotics in poultry -- Utilization of microorganisms for biopurification of wastewaters (agricultural and industrial): An environmental perspective -- From wastes to wealth: a Malaysian scenario -- Yeasts as probiotics for broilers -- Bacillus for rice cultivation: a case study in Thailand -- Microbial surfactant for preservation of natural rubber latex -- Microbial production of PHB for agricultural applications -- Applications of biofloc in aquaculture -- Bacteriocin for biopreservation of seafoods.
Keywords: Microbiology; Agriculture; Nutrition .; Wildlife; Fish; Microbiology; Agriculture; Applied Microbiology; Nutrition; Fish & Wildlife Biology & Management